Determination of Optimum pH and Temperature for Crude Extract of Lipase Enzyme from Sprouts Palm Oil Seeds (Elaeis guineensis Jacq) Against Hydrolysis RBDPO (Refined Bleached Deodorized Palm Oil) (Talenta Publisher, 2020)
Determination of optimum pH and temperature for crude lipase enzyme activity from oil palm seeds germination had been done. Oil palm germination is made by separating the seed from palm coconut soaking time process, drying, heated and seed germination in temperatures 39 to 40ºC during 60 days, 30ºC during 21 days, and 25ºC during 14 days. Centrifugations obtained crude lipase enzyme during 30 minutes with the speed of rotation 5000 rpm and 10000 rpm, and addition of (NH4)2SO4. Crude lipase enzyme diluted by buffer phosphate pH 7.0. The activity test of crude lipase enzyme done by measurement of free fatty acids levels obtained from hydrolysis process of RBDPO (Refined Bleached Deodorized Palm Oil) as substrate by titrimetric methods with temperature variations 300; 350; 400; 450; 500C and pH variations 6.0; 6.5; 7.0; 7.5 and 8.0